Del utillaje conceptual de la antropología: los usos del término “inductivismo” y los usos del término “hermeneútica”. Dos propuestas de clarificación - González Echevarría, Aurora (Revista de Antropología Social, 2006)
The reflections on the scope of the methodological concepts, as it happens in other contexts with “folk” or “theoretical” concepts, are useful to outline conceptual tools in Anthropology. This article seeks to solve problems that emerge when we do not take into account the different uses and meanings that terms may have within different methodological traditions. The interest for the different uses of the term “inductivism” is due to two apparent contradictions. The first one takes place between the adscription to the Tylor’s “inductive method” and Lakatos’ ideas. It does so by stating that the crisis of the inductivism in the XVII century led into the primacy of axiomatic-deductive methods in the XVIII and XIX centuries. The second one refers to the hypothetic-deductive method and grounded theory, often referred to as “inductivist”. In this text I will analyze different uses of “inductivism”. In one of them, which Popper criticized, it is assumed that nobody can be an inductivist. In another, backed by Bachelard, it is stated that no one can avoid being such. Something of the sort may be found within the debate on Anthropology and Hermeneutics. On that ground we should distinguish two different traditions: the ontological one -Heidegger, Gadamer-, which stress understanding as the key characteristic of social life, and the methodological/procedural one -Weber, Schütz, Ricoeur, Agar-. If we misunderstand and mix up both traditions, we may take Gadamer, instead of Agar or Ricoeur, as the model for the interpretation procedures and in doing so we may also wrongly contrast “hermeneutic” methodology to “scientific” methodology, without considering that interpretation is operated by means of hypothesizing on meaning –or hypotheses which include meaning themselves- and then putting these hypotheses to test. In that sense, hermeneutic “methodology” could only be regarded as scientific.
Keywords: Epistemology; Anthropological methodology; Inductive/deductive/abductive logic; Hypothetic-deductive methods; Grounded theory; Ontological hermeneutic; Procedures for interpretation; Comparison of theories